Storage efficiency comparison of UML models in selected database technologies - Filatov, Andrii; Flis, Paweł; Pańczyk, Beata (Journal of Computer Sciences Institute, 2019)
.The study answers the question which database is the best choice for efficient data storage of UML models. Three products were considered: MongoDB, PostgreSQL and Neo4J. The effectiveness test consists of measurement the response time of queries that save and load data. This study also take into account the memory increase ratio during data insertion and the level of complexity of the implementation of the test data mappers used in database queries.